(3fgL GdHdGZIs - (3Ydj Hf CHj WGdH,J (B40 (3g` s ((3Uaj GdOjf YHOGdeDef Hf jhSa Hf aGNQ s)
(3ChdgG (B:s
(3Edi Cf JYXe ef HdGFg eG cGf UZjQkG, hdG VYI CeQj Edi Cf JSJUZQ ef HdGFg eG cGf YXjekG s
(3BNQgG (B:s
(3aeG HcJ Ydjge GdSeGA hGdCQV, heG cGfhG oefXQjf BNQ GdLRA GdChd ef cJGH fgL GdHdGZI s
(3fSNI MGOjI YTQs
(3HgG fXGe GdJYbjHIs
(3hHYV JbWjY hWeSs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs